Relevance of Data in Construction Safety Prevention - Alfredo Soeiro (2023)
SHO This Symposium has been held annually since 2004, so SHO2023 will be its 20th edition. The publication of a book (since 2013) with chapters indexed in SCOPUS with great international projection has increasingly attracted the presence of delegates from many countries. Since 2019, SHO has offered technical-scientific training in the most varied areas, granting participation certification to those who register. Participants also have the opportunity to publish their work as one of the following manuscripts types: Book Chapter - written in English. All works that comply with deadline submission and the rules referred to in the authors' instructions can apply to Book Chapter. The works will be selected in two phases: Formal verification by the Occupational and Environmental Safety V Editors Scientific evaluation carried out by, at least, two members of the International Scientific Committee (ISC). Papers with an ISC average rating of 0 (or more points) on a scale from -3 to +3 points will be accepted. Unselected papers are automatically re-classified as Proceeding Articles for possible publication in the Proceedings Book. Proceeding Articles - written in Portuguese or English. This category includes articles selected by ISC's decision, according to the former point, or authors' submission option. Abstracts - written in English. This category includes articles selected by ISC's decision, according to the former point, or author's submission option. The abstracts will be considered for Poster presentation.